Preliminary report on the excavations of the legionary bath of Brigetio in 2024 - Dávid Bartus; Melinda Szabó; Rita Helga Olasz; Ákos Müller; Bence Simon; Lajos Juhász; Vilmos Lenár; László Borhy; Emese Számadó (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
The excavation of the legionary camp at Brigetio began in 2021. Throughout the last four campaigns, 2,200 square meters of the baths were unearthed, which span a total of well over 6,000 square meters. In 2024 the work continued across four surfaces. The excavations here shed a light on the size of the bath, which extended westward over a much larger area than previous excavations and radar surveys had suggested. In connection with the heating systems of the baths, two praefurnia preserved in excellent condition, along with their two adjoining service rooms, were also unearthed. In the southern section of the baths, three lime slaking pits were discovered, a rare occurrence in military context within the Roman Empire.